Determination of antibiotic residues in milk and assessment of human health risk in Bangladesh. Issue 8 (August 2021) - Rahman, Md. Sahidur; Hassan, Mohammad Mahmudul; Chowdhury, Sharmin
Abstract: Consumption of milk contaminated with antibiotic residues above the maximum residue limit (MRL) causes toxicity to humans and the development of superbugs that leads to the failure of antibiotic therapy and threatens human life. Moreover, long-duration exposure might alter the nature of gut microflora, resulting in the enhancement of many diseases. Therefore, our study aims to find out the residues level of selected antibiotics in milk and assessments of humans health risks. We examined 300 raw and processed milk samples using thin-layer chromatography (TLC) and ultra-high-performance liquid chromatography (UHPLC) methods against five veterinary antibiotics and assessed the health risk for consumers in Chattogram, Bangladesh. Risk analysis was done by using a hazard quotient based on 165 ml per capita milk consumption. We found a total of 7 % prevalence of antibiotic residues in raw milk, which were higher (8 %) in individual milk samples than the pooled samples (4 %). However, we did not find any antibiotic residues in processed milk. The mean concentration of oxytetracycline residue was detected at 61.29 μg/l, and amoxicillin was 124 μg/l in individual milk samples. Risk analysis showed that, the hazard quotient values are 0.0056 for oxytetracycline and 0.0017 for amoxicillin residues. This result implied no significant health risks associated with the consumption of milk produced and marketed in the study area. Our study might fill up the gaps of knowledge in measuring the safety status of milk regarding public health issues. Abstract : Antibiotic residue; Human health; Milk; Risk assessment; TLC; UHPLC.